1996
DOI: 10.1002/j.2048-7940.1996.tb01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Relationships and Adaptation to Spinal Cord Injury: A Qualitative Study

Abstract: To study adaptive processes following spinal cord injury, unstructured audiotaped interviews were conducted on an almost daily basis with a 30-year-old divorced male during the first 3 months of his initial comprehensive inpatient rehabilitation. Analysis of the transcribed tapes identified a number of important themes, including the theme of social relationships, recurring throughout the data. Family relationships are the focus of this article. The role of the rehabilitation nurse in promoting family involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…Seven papers of potential relevance were omitted from the review because they did not explore the experience of rehabilitation from patients' perspectives (the focus of this review) but specific, researcher-prioritized issues of goal setting, 38 clinical reasoning, 39 the role of the family, 40 adaptation to wheelchair use, 41 perceived rehabilitation needs 42 and the experience of hope. 43,44 Only two papers had sought explicitly to explore patients' perspectives of the experience of rehabilitation following SCI per se.…”
Section: Resultsmentioning
confidence: 99%
“…Seven papers of potential relevance were omitted from the review because they did not explore the experience of rehabilitation from patients' perspectives (the focus of this review) but specific, researcher-prioritized issues of goal setting, 38 clinical reasoning, 39 the role of the family, 40 adaptation to wheelchair use, 41 perceived rehabilitation needs 42 and the experience of hope. 43,44 Only two papers had sought explicitly to explore patients' perspectives of the experience of rehabilitation following SCI per se.…”
Section: Resultsmentioning
confidence: 99%
“…13 Several studies have shown negative effects of giving support on the quality of life of the caregivers of persons with SCI. 11,[14][15][16][17][18][19] Weitzenkamp et al studied stress and depression in 124 spouses of persons with SCI that had been injured more than 23 years ago. Spouses who were caregivers reported higher levels of stress, burnout, fatigue, resentment and depression compared to spouses who were not caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The adjustment process can result in a significant psychological burden. 3,4 Leisure as an important mechanism of coping with stress 5,6 has been discussed in the literature. Studies have documented that reduction or abandonment of leisure can lead to increased psychological distress.…”
Section: Introductionmentioning
confidence: 99%